Raised trappin2/elafin protein in cervico-vaginal fluid is a potential predictor of cervical shortening and spontaneous preterm birth. - Danielle S Abbott (Public Library of Science (PLoS), 2014)
Early spontaneous preterm birth is associated with inflammation/infection and shortening of the cervix. We hypothesised that cervico-vaginal production of trappin2/elafin (peptidase inhibitor 3) and cathelicidin antimicrobial peptide (cathelicidin), key components of the innate immune system, are altered in women who have a spontaneous preterm birth. The aim was to determine the relationship between cervico-vaginal fluid (CVF) trappin2/elafin and cathelicidin protein concentrations with cervical length in woman at risk of spontaneous preterm birth. Trappin2/elafin and cathelicidin were measured using ELISA in longitudinal CVF samples (taken between 13 to 30 weeks' gestation) from 74 asymptomatic high risk women (based on obstetric history) recruited prospectively. Thirty six women developed a short cervix (<25 mm) by 24 weeks' and 38 women did not. Women who developed a short cervix had 2.71 times higher concentrations of CVF trappin2/elafin from 14 weeks' versus those who did not (CI 1.94-3.79, p<0.0005). CVF trappin2/elafin before 24 weeks' was 1.79 times higher in women who had a spontaneous preterm birth <37 weeks' (CI: 1.05-3.05, p = 0.034). Trappin2/elafin (>200 ng/ml) measured between 14+0-14+6 weeks' of pregnancy predicted women who subsequently developed a short cervix (n = 11, ROC area = 1.00, p = 0.008) within 8 weeks. Cathelicidin was not predictive of spontaneous delivery. Vitamin D status did not correlate with CVF antimicrobial peptide concentrations. Raised CVF trappin2/elafin has potential as an early pregnancy test for prediction of cervical shortening and spontaneous preterm birth. This justifies validation in a larger cohort.